2020
DOI: 10.1051/e3sconf/202015101005
|View full text |Cite
|
Sign up to set email alerts
|

The use of transrectal massage combined with artificial vagina as semen collection in javan banteng (Bos javanicus) bull

Abstract: Semen collection in wild animals may be challenging for some methods such as electro ejaculator may cause pain and distress to the animals. Transrectal massage has been widely used in domestic and wild animals semen collection. Even though an artificial vagina may provide a condition that mimics the female reproductive tract and known to provide better results in some species, the application may face obstacles in the field. This study was conducted to evaluate the possibility of modified semen collection in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
0
1
3
Order By: Relevance
“…Terefore, our study's results were still below those of previous studies. Although not all the variables evaluated in the study showed signifcant diferences between the two banteng bulls, the value of progressive motility and viability of the Javan banteng spermatozoa in this study were still below the results of previous studies by Johnston et al [16] and Yoelinda et al [36].…”
Section: Discussioncontrasting
confidence: 93%
“…Terefore, our study's results were still below those of previous studies. Although not all the variables evaluated in the study showed signifcant diferences between the two banteng bulls, the value of progressive motility and viability of the Javan banteng spermatozoa in this study were still below the results of previous studies by Johnston et al [16] and Yoelinda et al [36].…”
Section: Discussioncontrasting
confidence: 93%
“…The results of the six batches showed a variation in the observed parameters. The The semen volume produced in this study is higher than the previously described by the electroejaculation method [13] and transrectal massage [17]. In the previous study [13,17], semen volume ranged from 4 to 7.4 mL (6.3±0.76) for electroejaculation and between 1 to 2 mL for transrectal massage combined with an artificial vagina.…”
Section: Resultscontrasting
confidence: 47%
“…The The semen volume produced in this study is higher than the previously described by the electroejaculation method [13] and transrectal massage [17]. In the previous study [13,17], semen volume ranged from 4 to 7.4 mL (6.3±0.76) for electroejaculation and between 1 to 2 mL for transrectal massage combined with an artificial vagina. It is well known that visual and olfactory stimuli play an essential role in male sexual behavior [21].…”
Section: Resultscontrasting
confidence: 47%
See 1 more Smart Citation